Answer:
.
Explanation:
According to the division property of exponents :
![(a^m)/(a^n)=a^(m-n)](https://img.qammunity.org/2021/formulas/mathematics/college/mxcs5cw0k5bw9j352q2bzzrm4zzfyd1t7v.png)
For example :
![(4^(5))/(4^(2))=4^(5-2)=4^3](https://img.qammunity.org/2021/formulas/mathematics/college/b0397mxlvjkmzevzxavevqh6g52rrca2ln.png)
Let's take one more example ,
![(5^(2))/(5^(3))=5^(2-3)=5^(-1)=(1)/(5)](https://img.qammunity.org/2021/formulas/mathematics/college/7ofsozd2xuvie4c6c5fs65fqkd6g4lo040.png)
The given expression :
![(e^2)/(e^(-4))](https://img.qammunity.org/2021/formulas/mathematics/college/1eo79k0slyaf5eqt934xjr74x8xjl2vfk9.png)
By division property of exponents , this will become
![(e^2)/(e^(-4))=e^(2-(-4))](https://img.qammunity.org/2021/formulas/mathematics/college/77steezxwovvg9bip9fipv5q1zz5no2y8t.png)
[Since (-)(-)=(+)]
Therefore , the required simplified expression would be
.